Spinocerebellar ataxia type 14: study of a family with an exon 5 mutation in the PRKCG gene. Issue 12 (16th November 2005) - Fahey, M C; Knight, M A; Shaw, J H; Gardner, R J McK; du Sart, D; Lockhart, P J; Delatycki, M B; Gates, P C; Storey, E
Abstract : We report our observations in an Australian family with spinocerebellar ataxia type 14 (SCA 14). We describe a novel mutation in exon 5 of the PRKCG gene, altering a highly conserved cysteine to a phenylalanine at codon 150, and record the detailed clinical observations in six affected family members.